Pain Management - Prostran, Milica (IntechOpen, 2016)
This book has seven chapters, from more than 15 authors from different countries (Korea, Poland, Saudi Arabia, Taiwan, Turkey and USA) edited by Professor Milica Prostran MD, PhD. The potential reader is shown the modern approach to pain management because the chapters deal at length and clearly with their topics. I believe that this book that I edited with great pleasure and dedication will capture the attention of many readers, from medical students to practicing doctors. All of them need to deal with this extremely important field of medicine: pain treatment. I do believe that the answers they may find in Pain Management will make their practice easier. Also, the life of their patients will be considerably more pleasant, or at least more bearable.